Educational Interventions in Diabetics With the Use of Health Belief Models: Literature Review - Irna Megawaty; Syahrul Syahrul (Indonesian Contemporary Nursing Journal, 2019)
The high prevalence rate in diabetes, causing diabetes is considered a health problem worldwide. Various studies related to interventions that can be done for diabetes sufferers have been widely carried out, including in terms of knowledge and education with the Health Belief Model (HBM) approach. The method used with the help of electronic data bases from journals that have been published through Pubmed, Wiley Online, Science Direct, Proquest, and Google Scholar. Results: 4 studies were included in the review, to assess the results of educational interventions in diabetics with the use of HBM. Conclusions and implications: It is known that the application of nursing education using the Health Belief Model concept framework has an effect on the self-management of diabetics so that it is expected to change patient compliance.